Game Theory for Resource Allocation in Heterogeneous Wireless Networks - A Review - Farhat Anwar; Mosharrof H. Masud; Burhan Ul Islam; Rashidah Funke Olanrewaju; Suhaimi Abd Latif (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In next-generation wireless networks, a user can be connected through Multi-Mode Device (MMD) to the multiple wireless networks in Heterogeneous Wireless Networks (HWN) considering several factors; including network technology, data service type, available bandwidth, Quality of Service (QoS), monetary cost, etc. To deal with all these multi attributes, game theory based models have been used to point out a better solution. This paper evaluates the techniques, methods, advantages, limitations of some game theory-based models for wireless resource allocation in HWN. Finally, it concludes that the Shapley Value method can be used for further research activities for its efficiency.